Encouraging Work Motivation and Organizational Commitment in Improving Employee Performance - Zaldhy Alvarizi Ramadhan; Muhammad Rizky Oktavian; Noveria Susijawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Research conducted at PT ΚΑΙ Persero DAOP 3 Cirebon focuses on empirical analysis of how work motivation and organizational commitment contribute to improving employee performance. This study applies a methodology based on a quantitative approach with associative problem formulation. This research aims as an observation in seeing the determinant factors that play a role in optimizing workforce performance. In this study, statistical analysis was conducted using multiple linear regression to explore the cause-and-effect relationship between independent and dependent variables. The research sample consisted of 106 respondents selected from a population of 144 permanent employees, using the Slovin formula-based sampling technique with a significance level of 5%. The research findings confirmed that work motivation has a significant impact on employee performance. Furthermore, organizational commitment is proven to have a positive impact on improving employee performance. These empirical findings confirm that the synergy between high levels of motivation and strong organizational commitment can create competitive employees and can improve the results oriented work climate. Furthermore, the implications of this research are expected to deepen the theoretical understanding of the relationship between the variables studied. Thus, this research can offer strategic recommendations for company management in formulating policies oriented towards increasing organizational effectiveness and efficiency.